2023
DOI: 10.1007/s11912-023-01415-3
|View full text |Cite
|
Sign up to set email alerts
|

Inequities Among Cancer Caregivers with Diverse Identities: A Review of the Literature and Future Directions

Abstract: Purpose of ReviewThe number of older adults with cancer relying on support from caregivers continues to increase. Health disparities in older adults with cancer often extend to their caregivers. This review aims to assess the state of cancer caregiving research in historically underrepresented diverse populations and provide recommendations for future research and policy. Recent Findings Research on caregivers of older adults with cancer from diverse backgrounds has primarily been descriptive. Health dispariti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…Inequitable access to physical and mental healthcare based on characteristics such as socioeconomic status and ethnicity is well established among the general population, and can be linked to variation in individuals’ abilities to seek and access healthcare services [ 58 62 ]. Similar equity concerns have been raised regarding support interventions for caregivers given certain dimensions of equity (e.g., culture, disability, religion, gender) are not often considered when interventions are developed and implemented [ 63 , 64 ]. Indeed, this study showed that caregivers with South Asian backgrounds felt culturally appropriate support was lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inequitable access to physical and mental healthcare based on characteristics such as socioeconomic status and ethnicity is well established among the general population, and can be linked to variation in individuals’ abilities to seek and access healthcare services [ 58 62 ]. Similar equity concerns have been raised regarding support interventions for caregivers given certain dimensions of equity (e.g., culture, disability, religion, gender) are not often considered when interventions are developed and implemented [ 63 , 64 ]. Indeed, this study showed that caregivers with South Asian backgrounds felt culturally appropriate support was lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, tailoring interventions based on caregiver’s cultural background may enhance intervention effectiveness [ 82 , 83 ], and has been found to improve the acceptability of interventions for caregivers in other settings [ 84 ]. Consideration of culture is also one dimension of equity which, as discussed above, requires further consideration during intervention development for caregivers [ 63 , 64 , 68 , 69 ]. Use of public contribution, engagement of caregivers with different cultural backgrounds during intervention development, and user-centred design approaches (e.g., creating personas) could be strategies to enhance acceptability and build empathy into interventions for caregivers [ 85 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer survivorship experiences and adequate caregiving in Black and Latinx communities are often marred by challenges, including limited access to health care, nancial constraints, and disparities in health care quality [10,11]. While cancer survivors navigate cancer diagnosis, associated health and lifestyle changes, and the implication of diagnosis on their relationship with families and communities, their caregivers may struggle with accepting the health condition of their loved one, balancing caregiving responsibilities and work, and may lack the resources to provide optimal care [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the caring tasks carers may take on during their care provision are administering at home cancer treatments, such as oral chemotherapy or medication injections, supporting people with cancer to manage the side effects of the treatment, such as pain relief, and daily hygiene management, such showering the person with cancer (Suter et al, 2021;Ussher et al, 2011). Some carers assist the person with cancer in accessing healthcare services through coordinating appointments with cancer specialists, assisting in treatment decision making, as well as providing transportation to appointments (Tan et al, 2023). For carers who share a home with the person with cancer they support, this often means taking on the domestic responsibilities that were once shared between a carer and the person with cancer (Balfe et al, 2016).…”
Section: Cancer Carer Responsibilitiesmentioning
confidence: 99%
“…Essentially, Māori carers who felt the disparity between their whānau cultural practices and the healthcare professionals reported taking up a communication role between the person with cancer and healthcare professionals (Walker et al, 2008). Māori carers took on their cultural caring role in various ways, including but not limited to, coordinating culturally informed traditional healing practices along with the western medical system and mediating between the person with cancer, whānau, and the healthcare system regarding medical decisions (Tan et al, 2023). Associated with the disparity between cultures, Māori carers were found to associate the healthcare system with stress, psychological distress, and feelings of disconnection and mistrust (Simpson et al, 2022;Slater et al, 2015).…”
Section: Māori Carersmentioning
confidence: 99%